Isoglosses In The Vocabulary Of Georgian Dialects Of Tao And Imereti - Gvantseladze, Gvantsa (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2016)
Two groups of the common vocabulary of the Georgian dialects - the dialect of Tao that is spread in the north-eastern part of the Republic of Turkey and Imeretian dialect are distinguished: 1.Words that are identical not only in both dialects but also they have the same phonetic, morphological and semantic structure in the Georgian literary language and most of its dialects; 2.Words that are slightly different phonetically but are identical in terms of semantics.